The role of cognition, affect, and resources in the influence of unreasonable tasks on work engagement: A moderated chain mediation model - Cheng, Hao; Li, Zhen; Zhao, Junshu; Wang, Weiqiang; Zou, Ruixi (Frontiers in Psychology, 2022)
Some studies have concentrated on the adverse effects of unreasonable tasks on work engagement. So far, however, the underlying mechanisms and boundary conditions of the relationship have not been adequately discussed. Based on the cognitive-affective systems theory and the job demands-resources model, this study constructs a chain mediation model in which unreasonable tasks influence work engagement through work alienation and negative affect and explores the moderating role of supervisor support in the model. An analysis of 427 questionnaires from multiple types of organizations shows that: Unreasonable tasks have a negative impact on work engagement; work alienation and negative affect play both separate and chain mediating roles in the negative effect of unreasonable tasks on work engagement, and supervisor support negatively moderates chain mediation by moderating the positive effect of unreasonable tasks on work alienation. This study re-investigates the relationship between unreasonable tasks and work engagement from cognitive, affective, and resource perspectives, which could be a valuable addition to established research and provide suggestions and assistance for management practice.